She Took Off Her Wings and Shoes - Bishop, Suzette (Utah State University, University Libraries, 2003)
May Swenson Poetry Award Volume 7, with foreward by Alicia Ostriker. Nominated twice for the Pushcart Prize, Ms. Bishop's credits include publications in Antioch Review, 13th Moon, Eratica, Aries, The Little Magazine, and many other literary journals. As a poet and writing teacher, she gives many readings, as well as workshops for gifted children, seniors, and other writers on the US-Mexico border; she has worked with at-risk youth and with the rural Hispanic community.